Pengaruh Harga, Kualitas Layanan dan Elektronic Word of Mouth terhadap Keputusan Pembelian pada Pelanggan Chila Petshop Kendari - Yusuf Yusuf; Muh Fakhrul Kamal; Muhammad Taufik; Triwulandari Nehru Putri; Ariawan Ariawan (Pusat Riset dan Inovasi Nasional, 2024)
The increasing trend of keeping animals has resulted in increased demand for pet food. The purpose of this study was to analyse the effect of price, service quality and electronic word of mouth on purchasing decisions. This research was conducted on 80 chila Petshop customers. The results of the study found that price, service quality and electronic word of mouth both partially and simultaneously have a positive and significant effect on purchasing decisions. so that traders can pay attention to this